An Analysis of Sociodemographic Patterns in Sudden Natural Deaths in a Tertiary Care Postmortem Center in Mumbai Region - Karthika J.; Bhalchandra Chikhalkar; Prabha K. (Indian Journal of Forensic Medicine and Pathology, 2025)
Background: Medico-legal autopsy is often warranted in cases of sudden and unexpected deaths. In the present study period, 2,267 such autopsies were carried out, with 222 cases (9.79%) identi𿿿ed as sudden and unexplained deaths. Theanalysis considered all natural deaths occurring within 24 hours from the onset of symptoms, as per the WHO de𿿿nition. Aim: The primary aim of this study is to examine the sociodemographic characteristics associated with sudden natural deaths. Objectives: To study the predominant age group involved, gender predominance, and to know about the socioeconomic groups in sudden death cases. Material: This prospective study was carried out in the Department of Forensic Medicine, Government Medical College, Mumbai, spanning a two-year duration from January 2020 to December 2022. Results: A total of 2,267 cases were brought for medicolegal autopsy to the mortuary, of which 222 were identi𿿿ed as sudden natural deaths, accountingfor 9.79% of the total. All autopsy cases where the cause of death was certi𿿿edas natural, along with those brought dead to the casualty without any evidence of unnatural cause, were included in the study. The distribution of these cases across various sociodemographic variables was examined, and all data were analysed using appropriate statistical methods with SPSS software. Conclusion: Sudden deaths can occur at any age, but the most common age group is 51-70 years, and it is more common in the Hindu religion and among the people of the lower middle class; therefore, raising awareness of associated risk factors and promoting early intervention may help mitigate the occurrence of such deaths.